Legal Protection and Equitable Carbon Benefit Sharing for Customary Forest Holders in Forestry Carbon Trading - Muslim Lobubun (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
This study analyzes legal protection and equitable carbon benefit sharing for customary forest holders within forestry-sector carbon trading under Presidential Regulation No. 98 of 2021 and Minister of Environment and Forestry Regulation No. 7 of 2023. It employs normative legal research using statutory, conceptual, and case approaches. The findings show that customary law communities holding a formal determination of customary forest status are recognized as actors in carbon trading, although such protection operates through conditional inclusion due to reliance on administrative formalization. Furthermore, tenure rights over customary forests do not automatically confer ownership of tradable Carbon Units. Regarding benefit sharing, current regulations mandate free, prior, and informed consent (Padiatapa), agreed benefit-sharing plans, reporting, evaluation, and grievance mechanisms, yet fail to establish substantive parameters to evaluate equitable distribution. To ensure comprehensive legal protection and substantive justice, this study proposes a rights-and-contribution-based carbon benefit-sharing framework built on four core parameters: recognition, consent, contribution, and distribution.